Pecking and Cannibalism in Laying Hens Raised in a Cage-free System in Western Bahia, Brazil - Tássia da Silva Costa, Naíla; Spinola Primo, Carla; Wilker da Conceição Santos, Marcos; Júlia Almeida Monteiro, Maria; dos Santos Conceição, Maurício; Talita Soares Frade, Maria; José Prazzi, Larissa; Santos, Flavia (Acta Scientiae Veterinariae, 2024)
Background: The methods used to raise animals have been questioned by consumers aware of animal welfare, causing the conventional method of raising animals in cages to be discussed. Cannibalism is described as one of the main problems faced in the intensive system of commercial breeding layers, due to the various stress factors that these birds are subjected to, such as high animal density, nutritional deficiency, lack of ambience and environmental enrichment. The objective of this study was to evaluate the occurrence of cannibalism practiced by chickens raised in the cage-free system in the municipality of Barra, West Bahia, Brazil. Cases: Laying hens without beak trimming raised in a cage-free system from the Embrapa 051 line showed cannibalistic behavior. According to the producer, of 650 layers, 60 died in around 30 days due to mutilation. Therefore, a technical visit was carried out to the property with the intention of investigating the motivation for this behavior. The birds are housed in a chicken coop 7 m wide and 15 m long, which is equivalent to a density of 6 birds/m². The environment was analyzed and, also the chicken facilities were observed, as well as, equipment such as waterers and feeders were evaluated. It was seen that the chicken coop is positioned in the north and south direction, which allows the sun to enter on both sides of this installation. The birds’ diet was based on soy, corn and kernels. There was no alternative food available for the chickens, and it was also noted that the animals were experiencing heat stress, as their wings and beaks were always open. On the day of the visit, 5 chickens were affected by the lesions. The extensive lesions on the back and vent caused by the chickens’ successive pecks drew attention. A necropsy was carried out on a chicken that died as a result of worsening injuries. Macroscopically, the absence of the intestines was noted. Discussion: The diagnosis of pecking and cannibalism was supported by clinical and pathological findings evidenced through technical visits and necropsies performed. The case shows that when purchasing birds without beak trimming, management becomes more challenging, as it is necessary to use resources to reduce cannibalism, such as environmental enrichment of the chicken coop with alternative suspended foods and the introduction of perches, which guarantees the temporary escape of chickens. Taking into account the information acquired both through the environmental assessment and the producer’s report, the relevance of technical support to small producers, responsible for planning actions aimed at mitigating losses related to the breeding system in which the layers are inserted. As intervention measures, the planting of moringa (Moringa oleifera) around the chicken coop, the sprinkling of water in the hottest periods with the aid of a backpack pump and environmental enrichment with suspended elephant grass (Pennisetum purpureum) and perches were encouraged. Therefore, investments aimed at animal welfare are necessary to minimize harmful behaviors that negatively impact egg production, such as cannibalism. Another point is the need for rural advisory programs that are more accessible to producers, since many of these problems are prevented with adequate technical guidance. Keywords: alternative poultry farming, animal welfare, egg production. Título: Bicagem e Canibalismo em Galinhas Poedeiras Criadas no Sistema Livres de Gaiolas no Oeste da Bahia, Brasil Descritores: avicultura alternativa, bem-estar animal, produção de ovos.